PERANCANGAN TATA LETAK DI PT. AEROWISATA CATERING SERVICE DENGAN MENGGUNAKAN METODE CRAFT (COMPUTERIZED RELATIVE ALLOCATION OF FACILITIES TECHNIQUES) - Ristyanadi, Bhiaztika; Orchidiawati, Nia (Media Mahardhika, 2019)
One of the quantitative methods used in the work are methods of repair facilities CRAFT (Computerized Relative Allocation of Facilities Techniques). CRAFT Method exchanging two or more departments to get the best layout and the biggest savings that can derived. Purpose of this research is to get the design layout and the optimal production facilities eligible activity corresponding relationships. The method used is Activity Relationship Chart (ARC) which is a simple technique in planning the layout of the facility. This method connects the activity in pairs so that all activities are known level of relationship. PT. ACS uses the combined type of layout which combines the type of layout based on the product and the type of layout by process or function. Type of product layout seen from the clustering of departments, each department producing products such as bakery and pastry department that produces only bread and pastry and fruits department only produces processed fruits and other divisions that manufacture products as per division.